THE EFFECT OF INFORMATION QUALITY ON PURCHASE DECISIONS THROUGH BRAND AWARENESS - Yuliana, Rahmi; Pantawis, Setyo (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of information quality on purchasing decisions for Ms.'s skincare products, mediated by brand awareness. This research uses a quantitative approach with the type of explanatory research. Respondents to this study were customers who had purchased skin care products more than twice in Semarang, with as many as 100 respondents using a judgmental sampling technique. Data analysis was performed using the Smart PLS analysis tool. The results showed that brand awareness has a positive and significant effect on purchase decisions, information quality has a positive and significant impact on purchase decisions, and brand awareness cannot mediate the influence of information quality on purchasing decisions.